2015
DOI: 10.4315/0362-028x.jfp-14-265
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of Tomatoes with Coliforms and Escherichia coli on Farms and in Markets of Northwest Nigeria

Abstract: Although recent reports indicated that produce contamination with foodborne pathogens is widespread in Nigeria, the sources and magnitude of microbial contamination of fruits and vegetables on farms and in markets have not been thoroughly identified. To ascertain possible pathways of contamination, the frequency and magnitude of coliform and Escherichia coli contamination of tomatoes produced in northwest Nigeria was assessed on farms and in markets. Eight hundred twenty-six tomato fruit samples and 36 irrigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 27 publications
1
11
1
Order By: Relevance
“…Sanitizers have been used for decontamination of pathogens; however, food safety and environmental concerns limit their use in agricultural produce (Lo & Martinez‐lo, ). Also, they are not highly effective for decontamination of food pathogens and often result in less than a 2‐log unit reduction of pathogens (Shenge, ). These reasons and many others such as the adverse effect of thermal treatment on the nutritional quality of food has increased the need for alternative means such as nonthermal treatment (Yang, Cao, Yang, Cai, & Zheng, ).…”
Section: Introductionmentioning
confidence: 99%
“…Sanitizers have been used for decontamination of pathogens; however, food safety and environmental concerns limit their use in agricultural produce (Lo & Martinez‐lo, ). Also, they are not highly effective for decontamination of food pathogens and often result in less than a 2‐log unit reduction of pathogens (Shenge, ). These reasons and many others such as the adverse effect of thermal treatment on the nutritional quality of food has increased the need for alternative means such as nonthermal treatment (Yang, Cao, Yang, Cai, & Zheng, ).…”
Section: Introductionmentioning
confidence: 99%
“…A study in Nigeria found that 50% of 336 irrigation water samples used for farming contaminated by E. coli > 126 MPN/100. The median value of E. coli contamination of tomatoes sold in a supermarket was 2.66 Log MP/g, which was higher than the contamination levels of tomatoes in farming areas (0.92 Log MPN/g) (Shenge et al, 2015). These studies suggest that E. coli contamination can occur in raw materials.…”
Section: Discussionmentioning
confidence: 61%
“…Similarly, the healthy and matured tomato fruit yield (FY) on each of the three treatment groups was measured in kilograms per square meter (kgm −2 ). Tomato fruit was collected using UV - sterile plastic bags and taken to the laboratory for immediate TC analysis following a serial dilution method ( Shenge et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%